Single-molecule DNA conductance in water solutions: Role of DNA low-frequency dynamics - Starikov, E. B.; Quintilla, A.; Nganou, C.; Lee, K. H.; Cuniberti, G.; Wenzel, W. (ELSEVIER, 2009)
Dependence of charge transmission through several experimentally studied DNA duplexes on their lowest-frequency acoustic modes, combined with the molecular dynamics in picosecond characteristic time range, has been studied. Based on this analysis we were able to identify the specific acoustic modes responsible for the noticeable increase in DNA charge transmission. Other factors influencing electric properties of DNA duplexes are discussed. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: AMBER; TEMPERATURE; COLLOQUIUM; TRANSPORT